Digital narratives: possibility of student protagonism in a pandemic context (Palíndromo, 2022)
This article aims to socialize the experiences lived with a project for the production of digital narratives in Elementary School II, carried out in the municipality of Dom Pedrito - RS, in a pandemic context. As a guiding question we have: How the production of digital narratives can contribute to the development process of student protagonism in the context of pandemic? To find the answers, we carried out a bibliographical research, basing the work on theorists such as Caldart (2012), Barbosa (2011), Sibilia (2012) and Bogo (2012). Subsequently, we carried out a field research, in which we used cell phones to produce photographs and subsequent montage of stop motion videos focusing on the daily lives of students. The production of digital narratives presents itself as a hybrid methodological possibility, which could meet the digital literacy of students, especially in the case of field students, who, concomitantly, in addition to studying, also work.
Keywords: Countryside Education; Art; Technology; Digital Narratives